1989
DOI: 10.1007/bf00332397
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and nucleotide sequencing of oxyR, the positive regulatory gene of a regulon for an adaptive response to oxidative stress in Escherichia coli: Homologies between OxyR protein and a family of bacterial activator proteins

Abstract: Treatment of Escherichia coli and Salmonella typhimurium cells with a low dose of hydrogen peroxide induces expression of a large number of genes, and confers resistance to oxidative stresses. The oxyR gene encodes a positive regulatory protein for a subset of these genes involved in the defense against oxidative damage. We cloned a DNA fragment that contains the E. coli oxyR region on a plasmid vector, and analyzed the nucleotide sequence of the gene. The amino acid sequence of OxyR protein, deduced from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…In this study we show that the redox-sensitive transcriptional activator OxyR, a member of the LysR-type family of bacterial transcriptional activators (9,36), is responsible for the control of the peroxide response regulon in this anaerobic microorganism. This is the first description of a functional oxidative stress response regulator in obligate anaerobic bacteria and in one so greatly diverged from the main line of eubacterial descent (41).…”
Section: Discussionmentioning
confidence: 81%
“…In this study we show that the redox-sensitive transcriptional activator OxyR, a member of the LysR-type family of bacterial transcriptional activators (9,36), is responsible for the control of the peroxide response regulon in this anaerobic microorganism. This is the first description of a functional oxidative stress response regulator in obligate anaerobic bacteria and in one so greatly diverged from the main line of eubacterial descent (41).…”
Section: Discussionmentioning
confidence: 81%
“…A recent map of the E. coli chromosome (22) suggested that the oxyR gene was located near the arg operon at 89.4 min; moreover, oxyR has recently been cloned and sequenced from the A 4G11 phage (40). Since the deduced oxyR restriction map perfectly matches that of the pMC7 plasmid from BamHI (bp 6850) to EcoRV (bp 8320), it has been proposed to map close to the arg operon (3,45).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this localization of the oxyR gene, we performed the following hybridization analysis. An oligonucleotide, whose sequence was derived from the oxyR DNA sequence (3,6,40,45), was hybridized to either restricted pMC7 plasmid DNA or restricted chromosomal DNA. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…amylovora RcsA protein was compared to the consensus sequence of the LysR family of bacterial activator proteins. The LysR family consists of at least 10 different bacterial proteins known to act as transcriptional activators (Henikoff et al, 1988;Tao et al, 1989), with each protein having a conserved helixturn-helix DNA binding motif near to its N-terminus. The observations that the Er.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided searches (Lipman & Pearson, 1985) of the NBRF, SWISSPROT and NEW NBRF protein databases failed to identify significant homology to any other protein sequences. In particular, no homology was found to either the LysR family of bacterial activator proteins (Henikoff, et al, 1988 ;Tao, et al, 1989) or to Cro-like DNA-binding proteins (Dodd & Egan, 1987).…”
Section: Methodsmentioning
confidence: 98%